PELATIHAN KEWIRAUSAHAAN TENTANG BISNIS RUMAHAN BAGI IBU RUMAH TANGGA DI DESA RENGASDENGKLOK SELATAN KECAMATAN RENGASDENGKLOK KAB KARAWANG - Ayu Fitri; Budi Rismayadi; Mumun Maemunah (Universitas Majalengka, 2020)
The implementation of community service activities aims to increase knowledge about home business so as to improve community welfare. Community service methods used are lectures and discussions. The material covers about home-based businesses that generate millions of turnover. The results obtained from this activity, all participants stated that this activity was very useful to increase knowledge and insight on how to take advantage of every home-based business opportunity.